Improvement Efficacy of Bacillus Subtilis Cellulose Hydrolyzing by Using Cold Plasma Technique - Hamza, Isam Shaker; Alzubaidi, Labeeb Ahmed; Jarallah, Aziz Latif; Ramadhan, Rehab S. (Iraqi Journal of Science, 2022)
Bacillus subtilis, an isolate of bacillus genus, was obtained from the laboratories of Ministry of Science and Technology. The best efficient Bacillus subtilis isolate in cellulose and semi-cellulose hydrolysis was treated with Dielectric-barrier Discharge (DBD). Atmospheric cold plasma technique (non-thermal) was used by exposing them at different times (2, 3, 4 and 5 mins) separately as a first stage, and then 60 seconds after any treatment separately as a second stage. After 48 hours, the difference between the plasma source and the sample was fixed at 0.5 cm. The results showed a variation in the growth of the isolate according to the exposure time by the appearance of culture turbidity and the estimation of optical density. Positive results appeared between exposure times, the amount of optical density, and the cellulose and semi-cellulose decomposition into glucose. Bacillus subtilis increased its efficacy in cellulosic hydrolysis and semi-cellulosic materials. Bacillus subtilis showed malleability and the ability to increase the efficiency in cellulose and semi-cellulose materials hydrolysis. We conducted a new and extensive study by using cold plasma technique to increase the hydrolysis efficacy of food microorganisms.